An exploratory use of the stakeholder approach to defining and measuring quality: the case of a cypriot higher education institution - Iacovidou, Melpo; Gibbs, Paul; Zopiatis, Anastasios (My University, 2009)
Cyprus has recently adopted laws to allow for the provision of private higher education. This case study concerns one such institution that is developing its understanding of quality through the eyes of two of its key stakeholders, staff and students. This empirical study is nested within the literature that advocates community-wide acceptance of quality assessment structures that reflect the views of the stakeholders. The purpose of this empirical study has been to define and assess quality in a Cypriot university using dimensions of quality as identified by two stakeholders (students and teachers) and the perceptions of the stakeholders. Importance-performance analysis was also used as a tool for identifying and prioritising areas for quality improvement purposes. The results identified a stakeholder-defined conceptual framework of quality dimensions. In addition, the results indicated a mismatch in student and teaching staff perceptions regarding the importance of factors in what constitutes quality higher education provision. The key differences are that students consider the programmes and courses of study offered by a higher education institution and the teaching and learning that takes place in the institution as the most important dimensions of quality higher education provision. Teaching staff, though, consider the student support services, the teaching and learning facilities and student examination and assessment as the most important dimensions
Keywords: Dimensions of quality; Stakeholders; Quality perceptions; Students; Academics; Cyprus